Bulk Operator Reconstruction in Topological Tensor Network and Generalized Free Fields - Xiangdong Zeng; Ling-Yan Hung (Entropy, 2023)
In this paper, we study operator reconstruction in a class of holographic tensor networks describing renormalization group flows studied in arXiv:2210.12127. We study examples of 2D bulk holographic tensor networks constructed from Dijkgraaf–Witten theories and find that for both the <semantics>Zn</semantics> group and the <semantics>S3</semantics> group, the number of bulk operators behaving like a generalized free field in the bulk scales as the order of the group. We also generalize our study to 3D bulks and find the same scaling for <semantics>Zn</semantics> theories. However, there is no generalized free field when the bulk comes from more generic fusion categories such as the Fibonacci model.